A six-nucleotide deletion polymorphism in the casp8 promoter is associated with reduced risk of esophageal and gastric cancers in Kashmir valley - Malik, Manzoor Ahmad (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Caspase-8 (CASP8) is a key regulator of apoptosis or programmed cell death, an essential defense mechanism against hyperproliferation and malignancy. To evaluate the role of CASP8 polymorphisms in esophageal (EC) and gastric cancers (GC) in the Kashmir valley, we examined the risk due to -652 6N ins/del polymorphism (rs3834129) in the promoter of CASP8 in a case–control study. MATERIALS AND METHODS: Genotypes of the CASP8 polymorphisms (-652 6N ins/del; rs3834129) were determined for 315 patients (135 EC and 108 GC) and 195 healthy controls by polymerase chain reaction. Data was statistically analyzed using Chi-square test and logistic regression model by using the SPSS software. RESULTS: Carriers for the del allele of rs3834129 single nucleotide polymorphism were associated with decreased risk for both EC (odds ratio [OR] = 0.278; 95% confidence interval [95% CI] = 0.090–0.853; P = 0.025) and GC (OR = 0.397; 95% CI = 0.164–0.962; P = 0.041). Also, in a recessive model, our results showed that CASP8 -652 6N ins/del “del/del” allele was conferring significant low risk for both EC (OR = 0.380; 95% CI = 0.161–0.896; P = 0.027) and GC (OR = 0.293; 95% CI = 0.098–0.879; P = 0.029). However, interaction of CASP8 -652 6N ins/del genotypes with smoking and high consumption of salted tea did not further modulate the risk of EC and GC. CONCLUSIONS: Polymorphism in CASP8 -652 6N ins/del polymorphism modulates the risk of EC and GC in Kashmir valley.